The Effect of Germination Time and Aloe vera Rind Ratio on Physicochemical and Nutritional Properties of Peanut Sprout Snack Bars: ROC-SAW Approach for Product Optimization - Narsih; Borneo Satria Pratama (Indonesian Scholar Society, 2025)
This study examined the effects of peanut germination time and the ratio of germinated peanut sprout flour to aloe vera rind flour on snack bar quality. Two experimental parameters were used in the study: flour proportions of 90:10, 80:20, and 70:30, and germination times of 12, 24, and 36 hours. The first evaluation concentrated on proximate composition, which included quantities of moisture, ash, fat, protein, fiber, and carbohydrates. Both factors and their interaction had a substantial (p < 0.05) impact on all proximal metrics. In order to determine the best formulation, these proximate data were then integrated into a multi-criteria decision-making framework using the Rank Order Centroid (ROC) and Simple Additive Weighting (SAW) techniques. The ROC–SAW results showed that the best combination of a 36-hour germination period and a 70:30 flour ratio yielded 23.79% protein, 8.81% fiber, 15.15% fat, and 31.37% carbohydrates. Additional analyses of the optimized formulation included antioxidant evaluation, amino acid profile, and FT-IR spectroscopy. FT-IR spectra revealed the presence of functional groups such as hydroxyl, carbonyl, amide, alcohol, and ether. Aspartic acid, glutamate, and arginine were the most frequently detected amino acids. The antioxidant activity IC50 value obtained from the DPPH experiment was 10,734.27 ppm. All things considered, combining germinated peanut sprout flour with aloe vera rind flour shows promise for producing a functional snack bar with enhanced nutritional content and bioactive potential.